Noninvasive detection of increased carotid artery temperature in patients with coronary artery disease predicts major cardiovascular events at one year: Results from a prospective multicenter study. (July 2017) - Toutouzas, Konstantinos; Benetos, Georgios; Koutagiar, Iosif; Barampoutis, Nikolaos; Mitropoulou, Fotini; Davlouros, Periklis; Sfikakis, Petros P.; Alexopoulos, Dimitrios; Stefanadis, Christodoulos; Siores, Elias; Tousoulis, Dimitris
Abstract: Background and aims: Limited prospective data have been reported regarding the impact of carotid inflammation on cardiovascular events in patients with coronary artery disease (CAD). Microwave radiometry (MWR) is a noninvasive, simple method that has been used for evaluation of carotid artery temperature which, when increased, predicts 'inflamed' plaques with vulnerable characteristics. We prospectively tested the hypothesis that increased carotid artery temperature predicts future cerebro- and cardiovascular events in patients with CAD. Methods: Consecutive patients from 3 centers, with documented CAD by coronary angiography, were studied. In both carotid arteries, common carotid intima-media thickness and plaque thickness were evaluated by ultrasound. Temperature difference (ΔT), measured by MWR, was considered as the maximal temperature along the carotid artery minus the minimum; ΔT ≥0.90 °C was assigned as high. Major cardiovascular events (MACE, death, stroke, myocardial infarction or revascularization) were recorded during the following year. Results: In total, 250 patients were studied; of them 40 patients (16%) had high ΔT values in both carotid arteries. MACEs occurred in 30% of patients having bilateral high ΔT versus 3.8% in the remaining patients ( p <0.001). Bilateral high ΔT was independently associated with increased one-year MACE rate (HR = 6.32, 95% CI 2.42–16.53, p <0.001, by multivariate cox regression hazard model). The addition of ΔT information on a baseline model based on cardiovascular risk factors and extent of CAD significantly increased the prognostic value of the model (c-statistic increase 0.744 to 0.845, p dif  = 0.05) Conclusions: Carotid inflammation, detected by MWR, has an incremental prognostic value in patients with documented CAD. Highlights: Microwave radiometry (MWR) allows noninvasive evaluation of carotid temperatures. Carotid temperatures predict the incidence of MACE in patients with CAD. Carotid temperatures offer incremental predictive value in current risk models. MWR could become an initial screening test for evaluation of vascular inflammation.